Evaluation of maturity levels in the management of product development: case studies in the capital goods industry - Jugend, Daniel [UNESP]; Silva, Sérgio Luis da; Toledo, José Carlos de; Onoyama, Márcia Mitiko (My University, 2010)
In recent approaches to the management of product development process (PDP), maturity levels have attracted the attention of practitioners and researchers. The CMMI model contributes to evaluate the maturity levels and improvement of the product development process management. This paper, based on CMMI model, analyzes the practices adopted in two companies of the capital goods industry, which develop and manufacture equipment upon request. It was observed that on account of market conditioning factors and different practices adapted to PDP management, these companies are at different maturity levels. One company is at the initial level of maturity while the other at the most advanced one. It was also noted that the application of CMMI model can provide improvement to PDP management, as well as present guidelines to achieve higher maturity levels, adequate to companies' needs.
Keywords: Product development process (PDP); Maturity model; Capital goods industry; Product development management